Analisis Investment Opportunity Set, Likuiditas, Profitabilitas, Leverage dan Ukuran Perusahaan Terhadap Kebijakan Pembayaran Dividen - M. Boy Singgih Gitayuda (Eco-Entrepreneur, 2022)
This study aims to obtain empirical evidence about the effect of investment opportunity set, liquidity, profitability, leverage and firm size on dividend payment policies in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. The population of this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange (IDX) in the 2015-2019 period. with a population of 61 companies and a sample of 18 companies was taken using purposive sampling method. The analysis method of this study uses multiple linear regression. The results of this study indicate that the investment opportunity set, liquidity, profitability, and firm size have a positive effect on dividend payment policy, and leverage has a negative effect on dividend payment policy.